Do Editors Hear the Voice of African Scholars? The Importance of Proactive Editorial Policies in Advancing Global IR - Oztig, Lacin Idil (SAGE PUBLICATIONS INC, 2026)
Africa remains one of the least represented continents in the discipline of International Relations (IR). Despite the continent's rich history and current importance in global affairs, African scholars continue to occupy a marginal position within mainstream IR debates. There is a rich literature on Global IR that critiques the dominance of Western-centric theories, concepts, and ideas in the discipline and calls for homegrown theorizing that reflects indigenous histories, experiences, and worldviews. In striving towards a truly inclusive and representative IR, journal editors have a crucial role to play. Mainstream editorial practices towards this goal include prioritizing articles on Global IR, diversifying the composition of the editorial board, appointing regional co-editors, and the like. This article argues that true inclusivity demands more than representational diversity. It necessitates proactive editorial policies that actively create opportunities for collaboration and dialogue among scholars. This Special Issue epitomizes this proactive editorial approach. The journal's editorial team reached out to African scholars through social media networks and Africa-focused WhatsApp groups, inviting them to co-author articles with members of the editorial board. Despite its modest scope, this initiative created a platform for collaboration, enabling authors to bridge institutional, regional, and intellectual boundaries. In addition to its objective of increasing African representation in IR scholarship, this initiative places journal acceptance rates under critical scrutiny, highlighting the potential of editorial intervention as an important step towards a more inclusive discipline. In other words, it brings a novel insight into the Global IR by focusing attention on editorial agency, which is an underexplored domain in the IR discipline.
Keywords: African scholars; editorial intervention; IR discipline; inequality; Global IR; CONSTRUCTIVISM; EUROCENTRISM; International Relations